The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10854-015-2784-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface modification of ceramic particles by SDS on the electrical properties of PZT-PVDF and BT-PVDF composites: interface effect

Abstract: Homogenous ceramic polymer composites of sodium dodecyl sulfate (SDS) modified BaTiO 3 (BT) and PZT particles as fillers and polyvinylidene fluoride (PVDF) as matrix have been developed using solution casting technique followed by hot pressing. XRD analysis confirmed the presence of both ceramic and polymer phase. The composites comprising of treated ceramic particles exhibited enhanced dielectric permittivity and reduced dielectric loss as compared with the untreated one. Furthermore, the energy density is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In addition, the diffraction peaks of SDS/BT-PVDF were almost the same as those of BT-PVDF, indicating that the addition of SDS did not change the crystal phase of the composite. 28 Figures 1 B and 1D are the SEM images of BT-PVDF and SDS/BT-PVDF composite films, respectively. Defects (such as pits and cavities) and aggregated BT particles can be clearly seen in the BT-PVDF films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the diffraction peaks of SDS/BT-PVDF were almost the same as those of BT-PVDF, indicating that the addition of SDS did not change the crystal phase of the composite. 28 Figures 1 B and 1D are the SEM images of BT-PVDF and SDS/BT-PVDF composite films, respectively. Defects (such as pits and cavities) and aggregated BT particles can be clearly seen in the BT-PVDF films.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the modification of ceramic nanoparticles by SDS can effectively improve the dielectric constant of composite films. 28 Some theoretical studies have also confirmed that the improvement of the flexoelectric effect can be achieved by increasing the dielectric constant of the composites by simulation. 8 , 29 However, there is no relevant experimental research to establish the relationship between particle dispersion, dielectric constant, and flexoelectric effect clearly at present.…”
Section: Introductionmentioning
confidence: 83%
“…BT nanoparticles can act as nucleating agents to induce the β-phase formation in P(VDF–TrFE), thereby improving the piezoelectric properties of the composites. 29,30 When P(VDF–TrFE)/BT membranes are applied for wound care under ultrasound therapy, the piezoelectric membranes activated by ultrasonic vibration can induce localized electrical stimuli to the target wound tissues, and subsequently affect the wound closure behaviors. 31–33 The combination of ultrasound and piezoelectric membranes is beneficial for the transmission of concentrated power energy that can penetrate into wound areas and further facilitate the wound healing process.…”
Section: Introductionmentioning
confidence: 99%
“…PZT ceramics and their compositionally modified variants with soft and hard dopants, all having an MPB composition, have been exploited in many sensor and transducer applications 5 . Owing to its tailorable properties, a lot of research work have been carried out recently to investigate the effect of various parameters, namely ceramic/matrix type 6 and ceramic-polymer interface 7–8 , in order to enhance the dielectric and piezoelectric properties of composites. This growing interest have opened up doors for a wide range of potential applications of piezoelectric composites 911 .…”
Section: Introductionmentioning
confidence: 99%